Critical Influenza and COVID-19—A Comparative Nationwide Case-Control Study. (16th May 2022) - Larsson, Emma; Eriksson, Jesper; Eriksson, Mikael; Oldner, Anders
Abstract : IMPORTANCE: Refined knowledge of risk factors for critical influenza and COVID-19 may lead to improved understanding of pathophysiology and better pandemic preparedness. OBJECTIVES: To compare risk-factor profiles of patients admitted to intensive care with critical influenza and COVID-19. DESIGN, SETTING, AND PATIENTS: A nationwide retrospective matched case-control study, including all adults admitted to an ICU in Sweden with influenza or COVID-19 between 2014 and September 2020 and a matched control population (ratio 1:5, patients:controls). MEASUREMENTS AND MAIN RESULTS: Admission to an ICU. The study included 1, 873 influenza and 2, 567 COVID-19 ICU patients, and 9, 365 and 12, 835 controls, respectively, matched on sex, age, and geographical region. Influenza patients were older and less likely male, and carried a larger burden of comorbidity and a higher Simplified Acute Physiology Score III score, whereas short-term mortalities were similar when compared to COVID-19 patients. The risk-factor profiles at ICU admission were largely comparable including socioeconomic, psychiatric, and several somatic variables. Hypertension was a strong risk factor in critical COVID-19 patients compared with influenza. Nonglucocorticoid immunosuppressive therapy was associated with critical influenza but not COVID-19. Premorbid medication with statins and renin-angiotensin-aldosterone system inhibitors reduced the risk for both conditions, the opposite was a seen for glucocorticoid medication. Notably, medication with betablockers, oral anticoagulation, and platelet inhibitors reduced the risk of critical COVID-19 but not influenza. CONCLUSIONS: The risk-factor profiles for critical influenza and COVID-19 were largely comparable; however, some important differences were noted. Hypertension was a stronger risk factor for developing critical COVID-19, whereas the use of betablockers, oral anticoagulants, and platelet inhibitors all reduced the risk of ICU admission for COVID-19 but not influenza. Findings possibly reflected differences in pathophysiological mechanisms between these conditions.